The importance of wine region and consumer s involvement level in the decision-making process - Madureira, Teresa (2014)
The purpose of this presentation is to identify and understand the relevant attributes, both extrinsic and intrinsic, that Portuguese consumers value and are relevant in the decision process for choosing wine. Further, the study aims to check possible differences in the valued attributes regarding consumer’s involvement level and wine Region Origin. The research was designed to identify relevant wine attributes and measure their importance when choosing a wine. In order to achieve this objective and match it with consumers’ involvement and wine origin region, 30 Focus Groups were performed, involving 171 consumers from five Portuguese regions of origin